Pancreatic adenocarcinoma during pregnancy. Case report - Lopes, César Vivian (2024)
Pancreatic ductal adenocarcinoma during pregnancy is extremely rare. Overall, including our case, only 19 cases confirmed antepartum have been reported to date. We report the case of a 37 year-old woman at 24 weeks of pregnancy in whom a pancreatic adenocarcinoma was identified during investigation of a suspected acute pancreatitis. Surgery was postponed until fetal maturity. However, chemotherapy was not tolerated, clinical condition of the mother worsened after cesarean section, and surgical findings revealed an unresectable disease. Patient died due to septic shock and multiple organ failure, but her child is in very good health. Pancreatic ductal adenocarcinoma during pregnancy carries the same poor prognosis of the general population. A pregnant with severe epigastric pain radiating to the back, in the presence of jaundice and weight loss, should rule out a pancreatic neoplasm. In case a malignancy is identified, the histology diagnosis is required, and decisions should be taken as a consensus between the mother and a multidisciplinary team in a referal center.